2022
DOI: 10.1109/tuffc.2022.3176742
|View full text |Cite
|
Sign up to set email alerts
|

Independent Component Analysis Filter for Small Vessel Contrast Imaging During Fast Tissue Motion

Abstract: Suppressing tissue clutter is an essential step in blood flow estimation and visualization, even when using ultrasound contrast agents. Blind source separation (BSS)-based clutter filter for high frame rate ultrasound imaging has been reported to perform better in tissue clutter suppression than the conventional frequency-based wall filter and nonlinear contrast pulsing schemes. The most notable BSS technique, singular value decomposition (SVD) has shown compelling results in cases of slow tissue motion. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…As shown by the results of our in vitro experiment, HOSVD provides 10 dB CBR improvement over AM when the probe is moving, compared to 5 dB improvement when the probe is static (where AM is generally working well in suppressing tissue signal). In the case of SVD, it has been reported that the spatiotemporal SVD filter's capability to detect flow is deteriorated when the flow speed is slower than the tissue motion velocity [14], [17], [18]. Hence, the nearly static microbubble flow in moving probe in vitro experiment and the in vivo and the myocardial perfusion are difficult cases for spatiotemporal SVD filtering because of the high spatiotemporal correlation between the microbubble and tissue signals when they are moving along.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by the results of our in vitro experiment, HOSVD provides 10 dB CBR improvement over AM when the probe is moving, compared to 5 dB improvement when the probe is static (where AM is generally working well in suppressing tissue signal). In the case of SVD, it has been reported that the spatiotemporal SVD filter's capability to detect flow is deteriorated when the flow speed is slower than the tissue motion velocity [14], [17], [18]. Hence, the nearly static microbubble flow in moving probe in vitro experiment and the in vivo and the myocardial perfusion are difficult cases for spatiotemporal SVD filtering because of the high spatiotemporal correlation between the microbubble and tissue signals when they are moving along.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that SVD suppresses tissue clutter better than conventional frequency filters and contrast pulsing schemes (AM and AMPI) [14]- [16]. However, its performance also degrades with slower flow rates and faster tissue motion since in that case the coherence between the contrast agent signal and tissue increases, thus preventing the separation into different components [14], [17], [18]. This is a crucial issue for cardiac imaging where tissue motion can reach up to 9.4 cm/s [19] and blood flow in the microcirculation is generally slower than 1 cm/s.…”
Section: Introductionmentioning
confidence: 99%